Avaliação da seletividade de inseticidas a trichogramma spp. (Hymenoptera: Trichogrammatidae) em diferentes hospedeiros - Goulart, R.M.; de Bortoli, S.A.; Thuler, R.T.; Pratissoli, D.; Viana, C.L.T.P.; Volpe, H.X.L. (My University, 2008)
The aim of this study was to evaluate the selectivity of pesticides to T. pretiosum and T. exiguum in different hosts. The tests were carried out using the LBCI (Laboratorio de Biologia e Criacao de Insetos) methodology based on the IOBC/WPRS methodology for selectivity studies. The hosts used were Anagasta kuehniella, Spodoptera frugiperda and Plutella xylostella eggs. The analysis of the selectivity was carried out for the products triflumuron (20 mL/100 L), etofenproxi (47 mL/100 L) and endosulfan (750 mL/100 L), with distilled water used as a control. Parasitized eggs, percentage of parasitism, percentage of emergence, longevity and sex ratio were evaluated in generations F1 and F2. Endosulfan was the most harmful, inhibiting the parasitism in all hosts. Etofenproxi showed low selectivity to parasitoids. Triflumuron was selective to parasitoid species when eggs of natural hosts were used.
Evaluation of the selectivity of insecticides to Trichogramma spp. (Hymenoptera: Trichogrammatidae) in different hosts.